Putting currency misalignment into gravity: The currency union effect reconsidered - Jan Hogrefe; Benjamin Jung; Wilhelm K. Kohler (University of Tübingen, Faculty of Economics and Social Sciences, 2012)
Member countries of a currency union like the euro area have absorbed asymmetric shocks in ways that are inconsistent with a common nominal anchor. Based on a reformulation of the gravity model that allows for such bilateral misalignment, we disentangle the conventional microeconomic trade effect and macroeconomic trade effects deriving from bilateral misalignment within currency unions. Econometric estimation reveals that for the euro area the misalignment channel exerts a significant trade effect on bilateral exports. We retrieve country-specific estimates of the misalignment-induced effect on trade which demonstrate heterogeneous outlooks across countries for the costs and benefits from adopting the euro.
urn:nbn:de:bsz:21-opus-61260
Keywords: F12; F13; F15; 330; Euro; gravity model; exchange rates; trade imbalances